Salvianolic Acid B, a Potential Chemopreventive Agent, for Head and Neck Squamous Cell Cancer - Zhao, Yuan (Hindawi Publishing Corporation, 2011)
Head and neck squamous cell cancer (HNSCC) is one of the top ten cancers in the United States. The survival rate of HNSCC has only marginally improved over the last two decades. In addition, African-American men bear a disproportionate burden of this preventable disease. Therefore, a critical challenge of preventive health approaches is warranted. Salvianolic acid B (Sal-B) isolated from Salvia miltiorrhiza Bge, which is a well-know Chinese medicines has been safely used to treat and prevent aging diseases for thousand of years. Recently, the anticancer properties of Sal-B have received more attention. Sal-B significantly inhibits or delays the growth of HNSCC in both cultured HNSCC cells and HNSCC xenograft animal models. The following anticancer mechanisms have been proposed: the inhibition of COX-2/PGE-2 pathway, the promotion of apoptosis, and the modulation of angiogenesis. In conclusion, Sal-B is a potential HNSCC chemopreventive agent working through antioxidation and anti-inflammation mechanisms.